2021
DOI: 10.3389/fcell.2021.631534
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Prognostic Signature for Gastric Cancer Based on Multiple Level Integration and Global Network Optimization

Abstract: Gastric Cancer (GC) is a common cancer worldwide with a high morbidity and mortality rate in Asia. Many prognostic signatures from genes and non-coding RNA (ncRNA) levels have been identified by high-throughput expression profiling for GC. To date, there have been no reports on integrated optimization analysis based on the GC global lncRNA-miRNA-mRNA network and the prognostic mechanism has not been studied. In the present work, a Gastric Cancer specific lncRNA-miRNA-mRNA regulatory network (GCsLMM) was constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, the five hub lncRNA genes give poor correlation with the survival prognosis of PTC patients by univariate Cox regression analysis. So based on this, we aim to investigate the prognosis features from their interacting miRNAs and target mRNAs, since much more prognostic signatures have been constructed using miRNAs and mRNAs in cancers, such as gastric cancer, endometrial carcinoma, and so on (Cui et al, 2021;Deng et al, 2021). Among 713 target miRNAs identified by the starBase v2.0, 17 miRNAs are demonstrated to be differentially expressed in TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the five hub lncRNA genes give poor correlation with the survival prognosis of PTC patients by univariate Cox regression analysis. So based on this, we aim to investigate the prognosis features from their interacting miRNAs and target mRNAs, since much more prognostic signatures have been constructed using miRNAs and mRNAs in cancers, such as gastric cancer, endometrial carcinoma, and so on (Cui et al, 2021;Deng et al, 2021). Among 713 target miRNAs identified by the starBase v2.0, 17 miRNAs are demonstrated to be differentially expressed in TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…In past decades, several bioinformatics strategies have been proposed to identify module biomarkers or key modules for tumorigenesis and development, on the basis of miRNet. Cui et al have integrated topological analysis and a random walk with restart algorithm to identify a prognostic signature for GC [19]. He et al have identified a module using a clique-percolation method with CFinder software, to divide patients into groups according to survival outcomes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulating studies have suggested that lncRNAs function as a competing endogenous RNA (ceRNA) via targeting miRNAs, forming a lncRNA-miRNA-mRNA regulatory axis [ 22 ]. Here, we discovered that NORAD was up-regulated in GC tissues, which enhanced GC cells’ proliferation and metastasis by regulating the miR-496/IL-33 axis.…”
Section: Introductionmentioning
confidence: 99%